Road Development and Poverty Reduction: The Case of Lao PDR - Peter Warr (Asian Development Bank Institute (ADBI), 2005)
Most poor people of the world reside in rural areas, which are frequently characterized by low levels of public infrastructure, especially roads. Inadequate roads raise transport costs, limiting the use poor people can make of local markets for the sale of their produce, the purchase of consumer goods and opportunities for off-farm employment. Between 1997–98 and 2002–03, rural poverty incidence in Lao PDR declined by 9.5 per cent of the rural population. This occurred even though some of the macroeconomic conditions in Lao PDR mitigated, to some extent, against the interests of rural people. The analysis of the relationship between poverty incidence and road development provided in this paper suggests that about 13 per cent of this decline in rural poverty can be attributed to improved road access alone. Other factors included a massive public investment in irrigation facilities. There is now a high return to providing dry weather access to the most isolated households of Lao PDR—those who have no road access at all. They constitute 31.6 per cent of all rural households in Lao PDR and are being left behind by the development of the market economy. By providing them with dry season road access, rural poverty incidence could be reduced permanently from the present 33 per cent to 29.7 per cent. A further reduction to 26 per cent could be obtained by providing all rural households with all-weather road access.
hdl:11540/4169
Keywords: 330; Verkehrsinfrastruktur; Straße; Verkehrspolitik; Armutsbekämpfung; Laos